2017
DOI: 10.3844/ajassp.2017.551.559
|View full text |Cite
|
Sign up to set email alerts
|

BlindLogin: A Graphical Authentication System with Support for Blind and Visually Impaired users on Smartphones

Abstract: Most graphical password systems on smart phones do not consider the needs of blind and visually impaired users. The main objective of this paper is to propose a new graphical authentication system which combines the usability of the graphical password with the security of the textual password and allows all types of users, including the blind and visually impaired users to use the same authentication system on a smartphone without any extra costs for special hardware. 84.6% of those surveyed would recommend Bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Moreover, with more people accessing the Internet from their Smartphones every year (see https://ourworldindata.org/age-structure ), and thus interacting with security mechanisms via soft keyboards, poor vision can present insuperable barriers to usage, unless the mechanism designed with accessibility in mind. Some noteworthy solutions explicitly accommodate this demographic [ 24 , 36 , 39 , 93 , 117 ].…”
Section: Accessibility and Vulnerabilitymentioning
confidence: 99%
“…Moreover, with more people accessing the Internet from their Smartphones every year (see https://ourworldindata.org/age-structure ), and thus interacting with security mechanisms via soft keyboards, poor vision can present insuperable barriers to usage, unless the mechanism designed with accessibility in mind. Some noteworthy solutions explicitly accommodate this demographic [ 24 , 36 , 39 , 93 , 117 ].…”
Section: Accessibility and Vulnerabilitymentioning
confidence: 99%
“…Moreover, to make Braille accessible on touchscreen, vibration feedback is proposed in Jayant et al [28,29] which showed promising results. Besides, BlindLogin approach is proposed in Ho et al [30]. This approach is compared in Schaub et al [31] with other graphical password authentication systems for people with visual impairments.…”
Section: Vibration For Touchscreen Accessibilitymentioning
confidence: 99%